2019
DOI: 10.7883/yoken.jjid.2018.248
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Effective Easy Competitive Enzyme-Linked Immunosorbent Assay Suitable for Monitoring Protective Immunity against the Rabies Virus in the Serum of Humans and Dogs

Abstract: The coverage of rabies vaccinations has been reported at 70-80% of dogs in annual reports. However, there are still outbreaks of rabies among humans and dogs in Thailand, thus indicating the necessity of ensuring seroprevalence in vaccinated dogs and efficacy of human immunization. A cost effective easy competitive enzyme-linked immunosorbent assay (CEE-cELISA) was developed here for monitoring protective immunity against the rabies virus in human and dog serum samples using monoclonal antibody clone 1-46-12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This study was performed to investigate the humoral immune response following primary and booster vaccination with the rabies virus glycoprotein and rabies vaccine in high-risk village volunteers. We confirmed that the participants were primed after receiving a cost-saving rabies PrEP vaccination independent of the achievement of seroconversion (anti-rabies antibody ≥ 0.7 EU/mL) as determined using the CEE-cELISA procedures from our previous study [ 11 ]. Our other study provided evidence that CEE-cELISA is suitable for monitoring antibodies against the rabies virus in the serum of humans compared with RFFIT results and revealed a very strong correlation between CEE-cELISA and RFFIT data [ 10 ].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…This study was performed to investigate the humoral immune response following primary and booster vaccination with the rabies virus glycoprotein and rabies vaccine in high-risk village volunteers. We confirmed that the participants were primed after receiving a cost-saving rabies PrEP vaccination independent of the achievement of seroconversion (anti-rabies antibody ≥ 0.7 EU/mL) as determined using the CEE-cELISA procedures from our previous study [ 11 ]. Our other study provided evidence that CEE-cELISA is suitable for monitoring antibodies against the rabies virus in the serum of humans compared with RFFIT results and revealed a very strong correlation between CEE-cELISA and RFFIT data [ 10 ].…”
Section: Discussionsupporting
confidence: 75%
“…The anti-rabies antibody levels in the three groups, PrEP and the 1st and 2nd booster groups, on D0, D28 and D180 were detected by CEE-cELISA. The lowest concentration of an anti-rabies antibody that could be detected by the CEE-cELISA was approximately 0.7 EU/mL, which was comparable with the REFFT result at 0.5 IU/mL [ 11 ]. On D0 before immunization and D28 after immunization, the median rabies antibody level was not different among the three groups; however, on D180, the median level in PrEP (16.5 EU/mL [95% CI 7.2–24.7 EU/mL) was significantly lower than that in the 1st booster group (25.8 EU/mL [95% CI 18.9–101.2 EU/mL]) and the 2nd booster group (27.0 EU/mL [95% CI 26.0–38.2 EU/mL]) (Fig.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations